Does partial muscle reinnervation preserve future re‐innervation potential?. Issue 6 (17th March 2017) - Isaacs, Jonathan; Mallu, Satya; Shall, Mary; Patel, Gaurangkumar; Shah, Pooja; Shah, Shalin; Feger, Mark A.; Graham, Gordon; Pasula, Nikhil
ABSTRACT: Introduction: Late revision nerve surgery for incomplete motor recovery due to partial reinnervation would improve muscle function if all muscle fibers were protected from developing denervation atrophy. Methods: Sixty immature Sprague‐Dawley rats underwent the following tibial nerve manipulations ( n = 15/group): group A, partial denervation (two thirds of nerve resected and the remaining one third crushed), revision repair at 8 months; group B, partial denervation; group C, complete denervation, immediate reconstruction; group D, complete denervation, reconstruction at 8 months; and group E, control. Final testing at 11 months included muscle force, weight, and histology. Results: Muscle weight was significantly ( P < 0.05) different among all groups (highest to lowest: E > B > C > A > D), and force was significantly lower in groups A and D compared with E. Muscle fiber cross‐sectional area was statistically smaller in group A than in groups B, C, or E. Discussion: Partial reinnervation still allowed substantial muscle recovery, but it did not preserve the non‐innervated muscle fibers. Muscle Nerve 56 : 1143–1148, 2017